2012
DOI: 10.2527/jas.2012-5236
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolites, milk yield, and physiological responses during the first week after kidding in Anglo-Nubian, Angora, Baladi, and Damascus goats under subtropical conditions

Abstract: This study was carried out to determine the level of certain biochemical variables reflecting the energy metabolic statuses during the first week of lactation in goats. A total of 120 Anglo-Nubian, Angora, Baladi, and Damascus does (30 does per breed) were used throughout 5 consecutive parities (30 does per parity) to investigate the effect of breed, parity, day of lactation, and their interaction on serum metabolites including total protein, albumin, globulin, glucose, total lipids, cholesterol, and transamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…Similar values were also observed in preprandial plasma of primiparous goats of different breeds during the first week after parturition (Anwar et al, 2012).…”
Section: Plasma Metabolitessupporting
confidence: 82%
“…Similar values were also observed in preprandial plasma of primiparous goats of different breeds during the first week after parturition (Anwar et al, 2012).…”
Section: Plasma Metabolitessupporting
confidence: 82%
“…Similarly to our results, DONIA et al (2014) also revealed that during lactation the activities of ALT and AST were comparable with those before pregnancy. However, throughout the first week of lactation, AST and ALT were lower in Angora goats than in Anglo-Nubian, Baladi, and Damascus goats (ANWAR et al, 2012). In our study, ALT tended to increase significantly at the end of lactation, while its value was non-significant in comparison to before gestation and the dry period.…”
Section: S a Allaoua And D Mahdi: Effect Of Physiological Status Ocontrasting
confidence: 80%
“…It is evident that the blood levels of various blood parameters can be used as criteria for diagnosis and prognosis of metabolic diseases, as well as for assessment of nutritional status (BALIKCI et al, 2007;KARAPEHLIvAN et al, 2007;TANRITANIR et al, 2009;BAGNICKA et al, 2014). However, in the last few years, many researchers have shown that the blood parameters of small ruminants are influenced by many factors such as age (MBASSA and POULSEN, 1991;ANTUNOvIC et al, 2017), geographical locations with different climates, gender, season, breed (AZAB and ABDEL-MAKSOUD, 1999;ANWAR et al, 2012;PICCIONE et al, 2012;DONIA et al, 2014;BAGNICKA et al, 2014;RIBEIRO et al, 2016), and the physiological stages of production (AZAB and ABDEL-MAKSOUD, 1999;IRIADAM, 2007;PICCIONE et al, 2011;DONIA et al, 2014;SADJADIAN et al, 2013). Several studies showed great variations in the levels of blood parameters between breeds of goats during the periods of pregnancy, parturition, and lactation (TANRITANIR et al, 2009;IRIADAM, 2007;WAZIRI et al, 2010;DARWESH et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In general, red cell parameters decrease during gestation and remain low for a few weeks post-partum as has been observed in cows, mares, sows, ewes, and bitches [ 12 ]. However, a great variation in hematological parameters exists between various breeds of goat [ 13 ].…”
Section: Discussionmentioning
confidence: 99%